The Effect Of The Application Of The Recitation Method On Mathematics Learning Outcomes Of Fifth Grade Students Of UPT SPF SD Inpres Rapokalling Tallo District Makassar City - Cahaya, Fitri; Sayidiman, Sayidiman; Nurhaedah, Nurhaedah (International Journal of Elementary School Teacher, 2023)
This study was conducted based on the problem of low student learning outcomes. The purpose of this study is to determine the description of the application of the recitation method, to determine the picture of learning outcomes mathematics UPT SPF SD Inpres Rapokalling 1 District Tallo Makassar. This research is included in experimental research with quantitative approach. The design used in this study is a quasi experiment with a type of nonequivalent control group design. The population in this study is all students of Class V UPT SPF SD Inpres Rapokalling 1 District Tallo Makassar. The samples in this study were 30 students of VA class and 32 students of VB class who were selected by purposive sampling technique. The Data in this study were collected using observation sheets, and student learning outcomes. The Data were analyzed using descriptive and inferential analysis. The results of descriptive analysis showed that the application of the recitation method went very well. The results of inferential analysis using an independent sample t-test showed that there were differences in pretest and posttest results between the experimental class and the control class which means that there is an increase in student learning outcomes in the experimental group better than the control group. So it can be concluded that: (1) the learning process by applying the method of recitation is very good; (2) student learning outcomes indicate an increase in student learning outcomes in learning; (3) there is an influence on the application of the method of recitation UPT SPF SD Inpres Rapokalling 1 District Tallo Makassar City